What is the teacher's challenge on the developing of learning media to increase critical thinking ability and the character? - Muhammad Sulthon; Pratiwi Pujiastuti; Heri Retnawati (Jurnal Prima Edukasia, 2021)
The development of technology makes learning media have an essential function for the learning process conducted by the teacher to students. However, in reality, there are still many teachers who have not yet implemented the development of learning media to support the learning program. The purpose of this study is to describe the challenges and problems that occur in the development of learning media to improve critical thinking skills and character. This study examines how the challenges of teachers in developing learning media to improve students' critical thinking skills and character. The method was in the form of qualitative data (phenomenology). Data were collected by conducting interviews and observations on nine teachers from 3 public elementary schools in Sleman Regency, Yogyakarta, Indonesia. Based on research, it conducted that students' critical thinking skills and character will increase if the teacher can solve or face challenges in developing existing learning media.